Effects of rehabilitation programs on heart rate variability after stroke: a systematic review - Belli, Thais Regina; Souza, Luciane Aparecida Pascucci Sande de; Bazan, Silméia Garcia Zanati; Bazan, Rodrigo; Luvizutto, Gustavo José (Arquivos de Neuro-Psiquiatria, 2021)
Background: It has been shown that the autonomic nervous system can be modulated by physical exercise after stroke, but there is a lack of evidence showing rehabilitation can be effective in increasing heart rate variability (HRV). Objective: To investigate the effectiveness and safety of rehabilitation programs in modulating HRV after stroke. Methods: The search strategy was based in the PICOT (patients: stroke; interventions: rehabilitation; comparisons: any control group; outcomes: HRV; time: acute, subacute and chronic phases of stroke). We searched MEDLINE, CENTRAL, CINAHL, LILACS, and SCIELO databases without language restrictions, and included randomized controlled trials (RCTs), quasi-randomized controlled trials (quasi-RCTs), and non-randomized controlled trials (non-RCTs). Two authors independently assessed the risk of bias and we used the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology to rate the certainty of the evidence for each included study. Results: Four studies (two RCTs with low certainty of the evidence and two non-RCTs with very low certainty of the evidence) were included. Three of them showed significant cardiac autonomic modulation during and after stroke rehabilitation: LF/HF ratio (low frequency/high frequency) is higher during early mobilization; better cardiac autonomic balance was observed after body-mind interaction in stroke patients; and resting SDNN (standard deviation of normal R-R intervals) was significantly lower among stroke patients indicating less adaptive cardiac autonomic control during different activities. Conclusions: There are no definitive conclusions about the main cardiac autonomic repercussions observed in post-stroke patients undergoing rehabilitation, although all interventions are safe for patients after stroke.
Keywords: Stroke; Heart Rate; Rehabilitation; Physical Therapy